EFIKASI DIRI MAHASISWA DALAM PENCARIAN INFORMASI DI WEBSITE PADA PERKULIAHAN ONLINE - Herry Hermawan; Natalina Nilamsari; Hamsinah Hamsinah (Universitas Prof. Dr. Moestopo (Beragama), 2023)
The COVID-19 pandemic caused learning to be done with an online system. Although much of the current literature recognizes the ability of the Internet as a medium of learning, less is known about students' self-confidence to use the Web, especially those who take part in online learning. This research is intended to understand students' abilities when using the Internet toward online information seeking. This study considers Self-Efficacy and Information Seeking Theory of online learning to examine influences of self-efficacy on behaviour toward online information seeking. Particularly, information seeking behaviour are explored as the consequences of belief in their capabilities to organize and execute the online learning. Data were collected through a quantitative study applying online questionnaire carried out in 2022, using a representative sample (N=58). Findings showed self-efficay has a strong correlation with information seeking behaviour. Self-efficacy also has a significant influence on information seeking behaviour. If self-efficacy increase, then information seeking behaviour will increase. The findings has contributed to the evolving of the Self-Efficacy and Information Seeking Theory, particularly in online learning in developing contries like Indonesia. This study provides implications to e-learning, educators, colleges, government and website system developers of online learning sites dealing with education.